1998
DOI: 10.1074/jbc.273.49.32522
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Protein-tyrosine Phosphatase Tyrosine Phosphorylation by c-Src during Platelet-derived Growth Factor-induced Mitogenesis Correlates with Its Subcellular Targeting

Abstract: The low molecular weight phosphotyrosine phosphatase (LMW-PTP) is an enzyme that is involved in the early events of platelet-derived growth factor (PDGF) receptor signal transduction. Our previous results have shown that LMW-PTP is able to specifically bind and dephosphorylate activated PDGF receptor, thus modulating PDGF-induced mitogenesis. In particular LMW-PTP is involved in pathways that regulate the transcription of the immediately early genes myc and fos in response to growth factor stimulation. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 23 publications
2
67
1
5
Order By: Relevance
“…It has been reported that the H 2 O 2 produced upon growth factor stimulation is really a cellular second messenger directly influencing many signal transducers such as the STAT proteins, p70 s6k, protein kinase D, and PTPs (33)(34)(35)(36). We have already demonstrated that LMW-PTP is a key regulator of PDGF-R phosphorylation upon recruitment to the membrane when cells are stimulated with the growth factor (5,6,10).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It has been reported that the H 2 O 2 produced upon growth factor stimulation is really a cellular second messenger directly influencing many signal transducers such as the STAT proteins, p70 s6k, protein kinase D, and PTPs (33)(34)(35)(36). We have already demonstrated that LMW-PTP is a key regulator of PDGF-R phosphorylation upon recruitment to the membrane when cells are stimulated with the growth factor (5,6,10).…”
Section: Discussionmentioning
confidence: 90%
“…Cell Lysate Fractionations-Cell lysate fractions were obtained as already described (6). Briefly, PDGF-stimulated NIH3T3 cells were lysed in RIPA buffer, and the lysates were clarified by centrifugation for 30 min at 20,000 ϫ g. Pellets were washed twice with 1 ml of RIPA and then resuspended in complete RIPA buffer (cRIPA), which is RIPA buffer plus 0.5% sodium deoxycholate and 0.1% sodium dodecylsulfate, by shaking for 1 h at room temperature and clarifying by centrifugation at 20,000 ϫ g for 30 min.…”
Section: Site-specific Mutagenesis and Cloning Of Lmw-ptp Mutants In mentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated previously that the cytoskeleton-associated fraction of LMW-PTP is phosphorylated by Src under PDGF stimulation in adherent cells (33). Such a phosphorylation seems fundamental for LMW-PTP association with p190Rho-GAP, which is phosphorylated only following PDGF stimulation (25).…”
Section: Lmw-ptp Did Not Affect Fes Phosphorylation (Right Panels)mentioning
confidence: 99%
“…Moreover, previous data have also demonstrated an involvement of LMW-PTP in the early events of PDGFr signal transduction. In fact, LMW-PTP by different mechanisms is able to specifically inhibit PDGF-induced NIH3T3 cell proliferation (14,18,19).…”
Section: Introductionmentioning
confidence: 99%